2011
DOI: 10.2754/avb201180010051
|View full text |Cite
|
Sign up to set email alerts
|

The acaricidal effect of flumethrin, oxalic acid and amitraz against Varroa destructor in honey bee (Apis mellifera carnica) colonies

Abstract: During 2007 and 2008, natural mite mortality was recorded in honey bee colonies. These colonies were then treated with various acaricides against Varroa destructor and acaricide efficacies were evaluated. In 2007, experimental colonies were treated with flumethrin and/or oxalic acid and in 2008 the same colonies were treated with flumethrin, oxalic acid or amitraz. The efficacy of flumethrin in 2007 averaged 73.62% compared to 70.12% for three oxalic acid treatments. In 2008, a reduction of 12.52% in mite numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Further evidence from multiple tests in Italy has revealed ≥95% varroa control when queen caging has been combined with OA applications, and this method has now been accepted as a standard treatment protocol (Nanetti et al 2016). It is interesting that, in colonies with brood, our four consecutive OA treatments were highly effective as compared with previous tests, where mortality ranged widely from 44 to 70% (Smodiš Škerl et al 2011). With capped brood present, reports of OA efficacy have been even more variable, ranging from 24 to 95% (Mutinelli et al 1997).…”
Section: Discussionmentioning
confidence: 59%
“…Further evidence from multiple tests in Italy has revealed ≥95% varroa control when queen caging has been combined with OA applications, and this method has now been accepted as a standard treatment protocol (Nanetti et al 2016). It is interesting that, in colonies with brood, our four consecutive OA treatments were highly effective as compared with previous tests, where mortality ranged widely from 44 to 70% (Smodiš Škerl et al 2011). With capped brood present, reports of OA efficacy have been even more variable, ranging from 24 to 95% (Mutinelli et al 1997).…”
Section: Discussionmentioning
confidence: 59%
“…The efficacy of Bayvarol has remained relatively high, killing 73–97 % of mites ( Smodiš Škerl et al 2011 , Olmstead et al 2019 ), though resistance to Bayvarol has also been reported ( Surlis et al 2016 , Table 3). PolyVar Yellow is flumethrin formulated as a strip.…”
Section: Chemical Control Of Varroamentioning
confidence: 99%
“…Los tratamientos contra Varroa consistieron en aplicar semanalmente y durante cuatro ocasiones 10 ml de amitraz (Taktic) al 1.25% en una toalla absorbente (Scott) de 28 x 6.5 cm sobre los cabezales de los bastidores de la cámara de cría. El uso de amitraz en dichas preparaciones se basa en previas investigaciones realizadas por Lupo y Gerling (1990), Smodiš et al (2011) y Gregorc y Planinc (2012) y en la probada efectividad del amitraz (Semkiw et al, 2013), la poca disponibilidad de acaricidas específicos para las abejas en México y la necesidad del experimento de garantizar la reducción significativa de los niveles de infestación, independientemente de las condiciones ambientales de cada época del año.…”
Section: Materials Y Métodosunclassified